Second Five Year Plan (1956-57 to 1960-61) Kolaba District Bombay State - Planning Commission (Planning Commission, 1958)
The Kolaba District lies between 18” and 19° North Latitude and 73° to 73.30’ East Longitude and covers an area of 2715 square miles. On the north it is bounded by Thana District; on the south by Ratnagiri District; on the east by Poona District and on the west by the Arabian Sea. the District forms a part of the Kokan strip and admeasures about 100 miles North to South. It is full of mountains and valleys, interspersed with low lands separated by creeks on the sea-side. There are 16 rivers flowing from cast to west. Most of the rivers are however seasonal and arc practically dry for 6 months of the year.
Bombay State